Language and power - Fairclough, Norman; Candlin, Christopher N. (London : Longman, 2001)
INHOUDSOPGAVE:##1. Introduction: critical language study##2. Discourse as social practice##3. Discourse and power##4. Discourse, common sense and ideology##5. Critical discourse analysis in practice: description##6. Critical discourse analysis in practice: interpretation, explanation, and the position of the analyst##7. Creativity and struggle in discourse: the discourse of Thatcherism##8. Discourse in social change##9. Critical language study and social emancipation: language education in the schools##10. Language and power 2000##Bibliography##Index
Onderzoek KASK (1KA-OFBG)
boek